Effects and mechanisms of Helicobacter pylori on cancers development and immunotherapy - Zhong, Xiaotian; Zheng, Huiling; Zhao, Shiqing; Wang, Ziye; Su, Yi; Zhong, Kaili; Wang, Mopei; Shi, Yanyan (Frontiers in Immunology, 2024)
Tumor immunotherapy has been widely used in clinical treatment of various cancers. However, some patients of these cancers do not respond to immunotherapy effectively. And H. pylori infection has been considered to be related to the efficacy of immunotherapy. This review aims to summarize the different effects and mechanisms of H. pylori infection on immunotherapy in different kinds of cancers. We searched the relevant literature on H. pylori and tumor immunotherapy, and summarized to form a review. Generally, H. pylori infection plays a role in affecting kinds of cancers’ development, besides gastric cancer. Current evidence suggests that H. pylori infection may reduce the efficacy of immunotherapy for colorectal cancer, non-small cell lung cancer and melanoma, but due to the lack of sufficient evidence, more data is needed to prove that. While for gastric cancer, the effects remain controversial. The H. pylori regulation effects and metabolisms involved in systematic related cancers should be paid attention to. Whether H. pylori should be eradicated when immunotherapy performed may be a critical consideration for some kinds of tumors.